O uso dos relatórios descritivos individuais como elemento articulador na transição das crianças da Educação Infantil para o Ensino Fundamental - Lins, Karina Graziela (2021)
The National Curricular Directives for Basic Education [Diretrizes Curriculares Nacionais Gerais para a Educação Básica] (DCNEB) present guidelines for conceiving and organizing our national educational system according to three basic dimensions: organicity, sequentiality and articulation. To organize and articulate the initial phases of Basic Education, official regulations determine that Kindergarten schools provide pedagogical documentation aimed at certifying and allowing continuity to children’s learning processes by creating adequate strategies for different moments of children’s transition. The São Paulo City Hall, thus, advises the building of individual descriptive reports, which must be sent to Elementary Schools and analyzed by first grade teachers in the beginning of the school year. Given this context, this research aims at investigating how first grade elementary school teachers of the city of São Paulo use the individual descriptive reports of kindergarten children during their school transition phase. This qualitative study used semi structured interviews with first grade elementary school three teachers and three pedagogical coordinators and sought to identify which pieces of information are considered relevant in their analysis of the reports; how they use data obtained from the reports; and which aspects should be considered for the construction of a formative action that ensures dialogue between Early Childhood Education and Elementary School. Data analysis used content analysis, based on Bardin (2016) and Franco (2018). A post-modern perspective on the concepts of Children, Childhood, Childhood cultures and School cultures supported the theoretical basis used to discuss our findings with the following authors: Barbosa (2007; 2014), Dahlberg; Moss and Pence (2019), Kramer (1987; 2006) Kramer, Nunes and Corsino (2011), Moss (2011), Julia (2001) and Frago (1995; 2007). Results revealed that there is misuse of the reports that get to first-grade teachers, and that such documents do not subside first-grade teachers’ planning, since the curriculum proposed to the Kindergarten and what is expected in terms of contents for such reports is unclear, in a way that its use is restricted to identifying children’s behavioral issues. We have also identified a lack of integrated training actions, aimed at articulating professionals both in Kindergarten and in Elementary School, and promoting reflections towards children’s transition between school phases and towards the potential uses of the reports in this process. Following the analysis, we proposed providing teacher and school management training that ensures the necessary dialog between Kindergarten and Elementary School, according to current legislations and to the teachers’ demands identified in this study